Corporate entrepreneurship behaviour in a South African financial services organisation - Mogopodi, Mogomotsi (My University, 2016)
Purpose The purpose of this study is to assess corporate entrepreneurship behaviour and identify elements that influence and promote corporate entrepreneurship in a South African financial services organisation. The study also defines corporate entrepreneurship and assists in gaining an understanding of corporate entrepreneurship behaviour in a context of a financial services organisation in the South African financial services sector. Data collection Online questionnaires were used to collect data. The online questionnaire was sent out to via email to employees at different hierarchal levels of a financial services organisation. The email contained a link which directed the participants to the online survey. Completed responses were sent back to a centralised system for collation with only one response per computer possible. Key findings The key findings of the study elucidate corporate entrepreneurship in a financial services organisation as not perceived as demonstrated and or used. There is a neutral sentiment towards CE which is widespread across the organisation regardless of hierarchal levels. Management support for corporate entrepreneurial activities was significantly low which goes to show that there by-in-large a low acceptance for CE. Key contribution This research contributes to the further improves the understanding of corporate entrepreneurship in financial services organisations in South Africa, and benefits. The study will additionally provide an improved understanding of the financial services industry. The outcome of this study will challenge executives in the insurance sector to consider the benefits of executing on corporate entrepreneurship intentions. To this end, the study adds value to the financial iii services sector and may potentially change how the players in this sector operate.
Thesis (M.M. (Entrepreneurship and New Venture Creation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Wits Business School, 2016.
Keywords: Entrepreneurship; Financial services industry--South Africa